(untitled) (RR Interdisciplinary Journal, 2024)
This paper aims to investigate how "loss of individuality" and "free will" function as tools of resistance in Lois Lowry’s The Giver. It examines how Jonas’s growing awareness of individuality and free will fuel his rebellion. This study explores the motivations behind the prohibition imposed on citizens in the so-called egalitarian society, which restricts their rights to live and pursue happiness, with a focus on the protagonist Jonas from The Giver and his intent to escape this society, as well as the achievements he attains after his departure. It also argues that the politically controlled society restricts the people from enjoying their rights and freedom to put them under its grip; and Jonas absconds from the authoritarian society to search his freedom, happiness and identity. It further analyzes the impact of loss of individuality and free will for the humanity and the protagonist Jonas. It concludes that losing one’s individuality and free choice hinder the growth of creativity, teamwork, and human existence in general. For analytical purposes, the study incorporates theoretical insights and available critical responses from scholars in the writing and theories of individuality and free will, including Hannah Arendt’s totalitarianism and individuality, Erich Fromm’s freedom and human development, and Michel Foucault’s power and resistance. Lastly, the study hopes to offer researchers a fresh perspective on the significance of individuality and free will for human development as a whole.